Rotator cuff unloading versus loading exercise program in the conservative treatment of patients with rotator cuff tear: protocol of a randomised controlled trial - Ann Cools; Larissa Pechincha Ribeiro; Paula Rezende Camargo (BMJ Open)
Introduction Atraumatic and degenerative rotator cuff tears are common in individuals over 55 years of age. This condition can have a high impact on social life and is associated with chronic pain, weakness and dysfunction of the upper limb. There is evidence that conservative approaches should be the first treatment option. Conservative treatment usually addresses a variety of therapeutic behaviours without providing scientific arguments for the choice and progression of exercises.Objective To compare the effects of two different exercise programmes based on the load of the rotator cuff on a population with shoulder pain and rotator cuff tears.Methods and analysis This is a controlled, randomised, blinded clinical trial. Seventy-eight individuals with shoulder pain and presence of atraumatic and degenerative rotator cuff tear will participate and will be randomly distributed between two groups. The primary outcome will be quality of life (The Western Ontario Rotator Cuff Index), and secondary outcomes will include pain, function (Disabilities of the Arm, Shoulder and Hand), fear avoidance beliefs (Fear Avoidance Beliefs Questionnaire-Brazil), kinesiophobia (Tampa Scale), Pain Catastrophizing Scale, muscle strength of abductors, external and internal rotators of the shoulder, range of motion of arm elevation and patient satisfaction. The treatment will be performed for 12 weeks (2 x/week) acording to the selected group (Rotator Cuff Unloading x Rotator Cuff Loading Exercise Programme).Ethics and dissemination The study protocol was approved by the Institutional Review Board. The findings of the trial will be disseminated through peer-reviewed journals and scientific conferences.Trial registration number NCT03962231.